ANALISIS PENGARUH JUMLAH PENDUDUK, TINGKAT PENDIDIKAN, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA TIMUR TAHUN 2017 – 2020 - Sari, Silvia Ayu Elvira; Pangestuty, Farah Wulandari (Journal of Development Economic and Social Studies, 2022)
East Java is one of the second largest contributors to Gross Domestic Product after DKI Jakarta, with a high GRDP, the unemployment rate should be overcome. However, when viewed from the unemployment rate, East Java has a greater number of unemployed compared to DKI Jakarta. This study aims to determine the effect of population, education level, and gross domestic regional product on unemployment in East Java in 2017 – 2020, a case of fifteen regencies and cities. This research is quantitative research with panel data. The results showed that the data is relieved from classical assumption’s problems, aside from that, population and education level have a significant positive on unemployment, meanwhile gross domestic regional product have a significant negative on unemployment.